EVALUASI KEBIJAKAN PENGENTASAN KEMISKINAN DI KECAMATAN SAMARINDA UTARA KOTA SAMARINDA (MENILIK PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI) - Daryono Daryono (Jurnal Administrative Reform, 2017)
This research aimed at investigating the implementation of National Program for Independent Community Empowerment (PNPM Mandiri) to alleviate poverty in North Samarinda sub district. Out of eight villages in North Samarinda sub district,  four were taken as the samples: Lempake, Sungai Siring, Tanah Merah and Budaya Pampang. Located in the suburban area, these villages were considered having higher poverty rate compared to the other four areas. Six criteria for evaluating public policy proposed by Dunn (2003) was used in this descriptive qualitative research. The criteria are effectiveness, efficiency, adequacy, equity, responsiveness and appropriateness.